2014
DOI: 10.1186/1755-7682-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Profile of idiopathic parkinson’s disease in Moroccan patients

Abstract: ObjectiveTo characterize clinical aspects of Idiopathic Parkinson’s disease from a movement disorders consultation in University Hospital of Rabat.MethodsRetrospective review of medical records of 117 patients with diagnosis of Idiopathic Parkinson’s disease seen in our outpatient clinic from 2006 to 2011.ResultsMean age was 64 ± 10 years with predominance of men (61.5%). Mean age at disease onset was 57 ± 11 years. Early onset Parkinson’s Disease was recorded in 12.8%. The median duration of disease was 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dystonia is a well-defined symptom in early onset Parkinson's disease (EOPD) as reported by Kilarski et al [ 39 ] in their systematic review and UK-based study of EOPD. The high frequency in our study can be explained somehow by the overall young age of onset of Parkinson's disease in Moroccan patients [ 40 ], but there was no statistically difference in age of onset between LRRK2 G2019S carriers and noncarriers ( p = 0.207).…”
Section: Discussionmentioning
confidence: 71%
“…Dystonia is a well-defined symptom in early onset Parkinson's disease (EOPD) as reported by Kilarski et al [ 39 ] in their systematic review and UK-based study of EOPD. The high frequency in our study can be explained somehow by the overall young age of onset of Parkinson's disease in Moroccan patients [ 40 ], but there was no statistically difference in age of onset between LRRK2 G2019S carriers and noncarriers ( p = 0.207).…”
Section: Discussionmentioning
confidence: 71%
“…The age at surgery of 54 years was in line with a Canadian series ( 38 ) but much lower than larger series where patients were operated between 58-61 years of age ( 36 , 37 , 42 ). This can be explained by the young age of onsetalready reported in our population with an age of onset < 55 years in 45% and < 45 years in 15% ( 43 ). The disease duration of 11.97 ± 4.28 years was similar to other series [15 16, 22, 23, 36–39, 42, 44].…”
Section: Discussionmentioning
confidence: 65%
“…The tremor-dominant phenotype was reported in 60% of the 65 studies 94,111,116 , with the classical rest tremor of the hand reported in 42.5% 99,129,203 . Non-motor symptoms have also been the focus of some studies with neuropsychiatric features, gastrointestinal symptoms, and cognitive impairments being the most frequently reported 109,125,129 .…”
Section: Clinical Featuresmentioning
confidence: 99%